Managing Complexity Through Consensus Mapping: Technology for the Structuring of Group Decisions - Hart, Stuart L.; Boroush, Mark; Enk, Gordon A.; Hornick, William (Academy of Management Review, 1985)
Stuart Hart, Mark Boroush, Gordon Enk, William Hornick, Managing Complexity through Consensus Mapping: Technology for the Structuring of Group Decisions, The Academy of Management Review, Vol. 10, No. 3 (Jul., 1985), pp. 587-600